The effect of caffeine on retinal vessel diameter in young healthy subjects - Terai, Naim; Spoerl, Eberhard; Pillunat, Lutz E.; Stodtmeister, Richard (Acta ophthalmologica (Oxford, England), 2012)
. Purpose:  To investigate the effect of caffeine on retinal vessel diameter before and during flicker light stimulation in young healthy subjects. Methods:  Seventeen healthy subjects (mean age: 29.6 ± 3.73 years, range: 22–35 years) were included in this study. The diameter of retinal vessels was measured continuously with the retinal vessel analyzer (RVA) before and 1 hr after 200 mg oral caffeine intake. After baseline assessment, a green luminance flicker of 20‐second duration was applied to stimulate retinal activity. The diameter of a segment of an arteriole and of a venule were measured during stimulation and 80 second after cessation of the stimulus. Flicker stimulation and 80‐second measurement interval were carried out three times. Blood pressure parameters, systemic mean arterial pressure (MAP), ocular perfusion pressure (OPP) and intraocular pressure (IOP) were obtained before and after oral caffeine intake. Results:  The mean diameter of the arterioles at baseline before caffeine intake was 123.30 ± 14.0 μm (arithmetic mean ± standard deviation) and after caffeine 117.30 ± 13.0 μm which was significantly different (p = 0.004). The mean diameter of the venules at baseline before caffeine intake was 147.60 ± 19.5 μm and after caffeine 137.73 ± 19.9 μm which was significantly different (p = 0.005). The mean diameter of the arterioles during flicker light stimulation before caffeine intake was 126.65 ± 13.24 μm and after caffeine intake 121.59 ± 12.12 μm (p = 0.012). The mean diameter of the venules during flicker light stimulation before caffeine intake was 151.87 ± 18.63 μm and after caffeine intake was 145.14 ± 19.82 μm (p = 0.027). The flicker response of the arterioles increased from 2.8% before caffeine to 3.8% after caffeine intake (p = 0.010). The flicker response of the venules increased from 3.4% before caffeine to 5.5% after caffeine intake (p = 0.0001). Baseline diameters and diameters during flicker light stimulation after caffeine intake showed a significant negative correlation to the MAP for the arterioles (baseline: r = −0.338, p = 0.049 and flicker: r = −0.345, p = 0.046) and the venules (baseline: r = −0.496, p = 0.003 and flicker: r = −0.479, p = 0.004). Conclusions:  The present study showed a significant vasoconstrictory response of the retinal vessels 1 hr after caffeine intake in young healthy subjects. Retinal vessel diameter changes were negatively correlated with MAP after caffeine consumption. These effects seem to be elicited by an autoregulatory response of the retinal vessels to the increased blood pressure changes after caffeine.